The use of the Court program and its impact on engineering thinking among the second -grade students (Journal of the College of Basic Education, 2022)
The aim of the current research is to identify the use of the CORT program and its impact on the geometric thinking of the students of the second intermediate grade in mathematics.In order to verify the objective of the research, the following null hypothesis was put forward:• There is no statistically significant difference at the level of significance (0.05) between the average scores of the students who study according to the Cort thinking program and the average scores of the students who study according to the usual method in the engineering thinking test.